Strategi Pengembangan Sistem Insentif yang Berkeadilan bagi Tenaga Penjualan dalam Meningkatkan Daya Saing Organisasi - Rini Falensia; Medy Idrian Witrisna; Arisandi Arisandi; Sentot Imam Wahjono (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study addresses the low effectiveness of human resource (HR) strategies, which affects employee performance and organizational outcomes. The purpose is to examine the effectiveness of a fair incentive system for sales personnel and strategies for its development to enhance organizational competitiveness. Using a library research method, secondary data were collected from scientific journals (2020-2025) via the Publish or Perish application. Data were analyzed qualitatively and descriptively through content analysis, comparing perspectives from various studies to identify similarities, differences, and research gaps. Findings indicate that a fair incentive system enhances motivation, productivity, and loyalty when it applies principles of fairness in distribution, procedures, and interactions. Effective incentive strategies integrate financial and non-financial rewards, leverage innovation and digital tools, and promote two-way communication. Combining individual and group incentives fosters team synergy and strengthens organizational competitiveness. The study highlights that transparent and performance-relevant incentives are essential for sustainable HR development and organizational success.